Optimization of Fooder Sorghum (Sorghum Bicolor L. Moench) Growth in a Closed Hydroponic System Through Combination of Red and Blue LED Lighting - Radi Radi; Yuwan Nanda Adyatma; Makbul Hajad (The University of Lampung, 2022)
Plant cultivation with a closed hydroponic system needs to be developed as a food production solution in the future. With this technology, plant growth parameters (including light parameters) can be adjusted according to needs so that plants can grow optimally. Red and blue light are needed for sorghum cultivation. This study aims to analyze the effect of the combination of red and blue LED lights on the growth of sorghum plants and determine the optimal ratio between the two light sources based on the plant growth rate in a closed hydroponic system. The plant growth parameters measured included plant height, stem diameter, number of leaves, leaf area, leaf color, wet weight, dry weight, water consumption, and morphology of sorghum plants. This research is conducted by constructing the nine combination of red and blue LED light with the control system placed inside each closed hydroponic box. The results confirmed that the use of red and blue LED light combinations has a significant effect on the growth rate of sorghum. The optimum combination of red and blue LED light is obtained from combination of R7:B1 with the conversion ratio of 9.53 kg fresh product per kg sorghum seed. Keywords: Closed Hydroponic System, Control Systems, Growth Optimization, Sorghum Plant, Red And Blue LED Light